Effect of Height on Perceived Exertion and Physiological Responses for Climbers of Differing Ability Levels - Gajdošík, Jan; Baláš, Jiří; Draper, Nick (Frontiers in Psychology, 2020)
Purpose. The purpose of this study was to examine differences in perceived exertion (RPE) and physiological responses for climbers of different abilities completing an identical route low and high above the ground. Materials and Methods. Forty-two male (N=18) and female (N=24) sport climbers divided in three groups, lower grade (N=14), intermediate (N=14) and advanced climbers (N=14), completed two visits to a climbing gym separated by 7 days. In a random order, the climbers completed a close to the ground ascent (treadwall) and climb to height (climbing gym). Immediately after the test, climbers provided their RPE (6 to 20). Indirect calorimetry was used to assess physiological response during the ascent and recovery. Results. The mean (± standard deviation) RPE was higher for lower grade climbers when ascending the route on the wall (RPE = 12±1) when compared to the treadwall route (RPE=11±1, P = 0.040; d = 0.41). For all ability groups, the physiological response was higher on the climbing gym wall as opposed to on the treadwall; ventilation (P = 0.003, μp2 = 0.199), heart rate (P = 0.005, μp2 = 0.189), energy cost (P = 0.000, μp2 = 0.501). The RPE demonstrated moderate relationship with physiological variables (R2= 0.14 to R2= 0.45). Conclusion. Climbing to height induced a greater metabolic stress than climbing at a low height (treadwall) and led to higher RPE for lower grade climbers. In this study RPE appeared to be a good proxy measure of the physiological demands for advanced climbers but not for intermediate and lower grade climbers. Therefore, using RPE in climbing with less experienced athletes may perhaps overestimate actual exercise intensity and should be interpreted carefully.